The missing manatee - DeFelice, Cynthia C. (New York, NY : Scholastic Inc., 2007)
While coping with his parents' separation, eleven-year-old Skeet spends most of Spring Break in his skiff on a Florida river, where he finds a manatee shot to death and begins looking for the killer.
G10
Keywords: Boats and boating -- Fiction; Fishing -- Fiction; Family problems -- Fiction; Manatees -- Fiction; Mystery and detective stories; Florida -- Fiction